2007
DOI: 10.1097/mlg.0b013e318145386c
|View full text |Cite
|
Sign up to set email alerts
|

Incision and Drainage Followed by Mattress Suture Repair of Auricular Hematoma

Abstract: Incision and drainage followed by through-and-through absorbable mattress sutures appears to be a superior method of treatment with rare reaccumulation of hematoma. This method of treatment was shown to be simple and well tolerated, and it had few complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 13 publications
1
32
0
2
Order By: Relevance
“…The disease is frequently associated with a history of trauma. 6 The present study revealed that the pseudocysts occurred at the scaphoid fossa with triangular fossa of pinna without any evident aetiological factor in most of the cases. As per a study, the aim of management of the condition is to restore the normal appearance of pinna that could be achieved by removal of the cystic content by aspiration or incision followed with induction of fibrosis of intra-cartilaginous cavity reinforced by bilateral pressure dressing.…”
Section: Discussionmentioning
confidence: 89%
“…The disease is frequently associated with a history of trauma. 6 The present study revealed that the pseudocysts occurred at the scaphoid fossa with triangular fossa of pinna without any evident aetiological factor in most of the cases. As per a study, the aim of management of the condition is to restore the normal appearance of pinna that could be achieved by removal of the cystic content by aspiration or incision followed with induction of fibrosis of intra-cartilaginous cavity reinforced by bilateral pressure dressing.…”
Section: Discussionmentioning
confidence: 89%
“…The aim of treatment should be to restore the normal contours of the ear and prevent infection. Prompt surgical intervention under good antibiotic cover as applied in our patients achieved this [3][4][5][6][7][8]. Pressure dressing following surgical drainage helped to avoid re-accumulation in case of haematoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, auricular injury in a child without a confirmed history of trauma should raise the suspicion of a possible child abuse [1] as in bilateral ear injuries in children less than 1 year of age [2]. Lesions encountered include swelling or haematoma [3][4][5][6][7][8], Lacerations [2,4], abrasions or even complete avulsion. Middle ear injury frequently results from direct trauma through the external auditory canal.…”
Section: Introductionmentioning
confidence: 99%
“…Auch wenn die Punktion von Othämatomen noch durchaus Verwendung findet, sollte die alleinige Punktion des Othämatoms/-seroms kritisch gesehen werden, da dies auch bei frischen Hämatomen oft zu Rezidiven führt [8]. Auf jeden Fall muss eine längerfristige postoperative Kompression mittels durchgreifender Matratzennähte oder individuell geformter Abdrücke der Ohrmuschel erfolgen.…”
Section: Othämatom Und -Seromunclassified